PENGARUH LITERASI KEWIRAUSAHAAN DAN INTELLECTUAL AGILITY TERHADAP INTENSI BERWIRAUSAHA SISWA (Survei Pada Siswa Kelas X dan XI SMK Yapsipa Tasikmalaya) - Yunira Utari; Rendra Gumilar; Edi Fitriana Afriza (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The problems related to the research are based on the low entrepreneurial intention among students as seen based on the tracer study of alumni of SMK Yapsipa Tasikmalaya which shows a very low entrepreneurial rate. The purpose of this research is to determine the effect of entrepreneurial literacy and intellectual agility on students' entrepreneurial intentions, where the focus of the research is directed at students in grades X and XI of SMK Yapsipa Tasikmalaya who are expected to have the potential to become young entrepreneurs. The research method used is quantitative with an explanatory survei and data collection techniques using questionnaires via Google forms and documentation. The research population was students in grades X and XI at SMK Yapsipa Tasikmalaya in the 2024/2025 academic year totaling 71 students. The sample used was a saturated sample taken from the entire population, consisting of 32 students in grades X PM and X MPLB, and 39 students in grades XI MP, XI BR, and XI AK. The data analysis technique used is multiple linear regression analysis to determine the effect of each independent variable on the dependent variable processed using SPSS version 23. Based on the results of the study, both partially and simultaneously, it shows that the hypothesis is accepted.